Variable mechanism of nucleophilic substitution of P-stereogenic phosphoryl chloride with alkynyl metallic reagents. Issue 5 (24th December 2015) - Yao, Lan; Liu, Li-Juan; Xu, Zhong-Yuan; Nie, Shao-Zhen; Xiao, Xiao-Qing; Zhao, Chang-Qiu
Abstract : The variable mechanism for substitution of P -stereogenic phosphoryl chloride with alkynyl metallic reagents depends on temperature, stoichiometry of starting materials, and the structure of the nucleophilic reagent. Abstract : The variable mechanism for substitution of P -stereogenic phosphoryl chloride with alkynyl metallic reagents, which depends on temperature, stoichiometry of starting materials, and the structure of the nucleophilic reagent, is assumed as either SN 2-like or Berry pseudorotation of pentacoordinated phosphorus intermediates, affording inversion and retention products, respectively. The formation of the inversion product can be controlled to occur predominantly to afford ( R P )-alkynylphosphinates.